2021
DOI: 10.1101/2021.01.04.425268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell RNA-seq and Mass Cytometry Reveals a Novel and a Targetable Population of Macrophages in Idiopathic Pulmonary Fibrosis

Abstract: In this study, we leveraged a combination of single cell RNAseq, cytometry by time of flight (CyTOF), and flow cytometry to study the biology of a unique macrophage population in pulmonary fibrosis. Using the profiling data from 312,928 cells derived from 32 idiopathic pulmonary fibrosis (IPF), 29 healthy control and 18 chronic obstructive pulmonary disease (COPD) lungs, we identified an expanded population of macrophages in IPF that have a unique transcriptional profile associated with pro-fibrotic signature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 92 publications
2
26
0
Order By: Relevance
“…Furthermore, Ayaub et al . ( 45 ) analyzed the data reported by Adams et al . ( 44 ) in detail and found that in addition to a similar increase in SPP1 hi macrophages, these macrophages have intermediate features between AMs and IMs.…”
Section: Role Of Macrophages In Pfmentioning
confidence: 99%
“…Furthermore, Ayaub et al . ( 45 ) analyzed the data reported by Adams et al . ( 44 ) in detail and found that in addition to a similar increase in SPP1 hi macrophages, these macrophages have intermediate features between AMs and IMs.…”
Section: Role Of Macrophages In Pfmentioning
confidence: 99%
“…Highly proliferative osteopontin-expressing macrophages were identified through scRNA-seq and were found to mediate myofibroblast activation in the lungs of IPF patients (155). Similarly, another expanded population of pro-fibrotic CD36 + CD84 + macrophages in IPF were identified, which also showed increased expression of genes involved in ECM remodeling (156,PREPRINT).…”
Section: Macrophagesmentioning
confidence: 99%
“…LAMs and LAM-like cells have been observed in disease contexts in adipose tissue from obese human individuals and from mice (Jaitin et al, 2019), injured and fibrotic liver (Perugorria et al, 2019;Ramachandran et al, 2019;Xiong et al, 2019), fibrotic lung (Ayaub et al, 2021;Reyfman et al, 2019), atherosclerotic aortic tissue (Cochain et al, 2018;Willemsen & de Winther, 2020), and Alzheimer's disease brain (Grubman et al, 2019;Keren-Shaul et al, 2017;Mathys et al, 2019). However, an understanding of their distribution and heterogeneity across human tissues is still lacking.…”
Section: Lam-like Macrophages Are Prevalent Across Human Tissues In Health and Disease And Are Associated With A Shared Regulatory Programentioning
confidence: 99%